What Happens on the Field Stays on the Field: Exploring the Link between Football Player Penalties and Criminal Arrests. Issue 11 (2nd November 2017) - Leal, Wanda; Gertz, Marc; Piquero, Alex R.; Piquero, Nicole Leeper
ABSTRACT: Research in organizations has tended to focus only on performance in the workplace and until recently has not paid much attention to behavior outside of the workplace. Conversely, the limited research on crime in the National Football League (NFL), the type of organization we study, has focused largely on misbehavior off-the-field. We confluence these lines of research by focusing on both on-duty and off-duty behaviors. We examine the relationship between on-duty behavior, measured through both the number of penalties and total penalty yards accumulated by an NFL player, as well as their off-duty behavior, measured through criminal arrests. Findings show that a higher number of penalties and a higher total number of penalty yards is associated with more total arrests, more nonviolent arrests, but has no effect on violent arrests. These findings hold in the regular but not post-season.